Anti-Inflammatory Effects of the Mediterranean Diet in the Early and Late Stages of Atheroma Plaque Development. (18th April 2017) - Casas, Rosa; Urpi-Sardà, Mireia; Sacanella, Emilio; Arranz, Sara; Corella, Dolores; Castañer, Olga; Lamuela-Raventós, Rosa-María; Salas-Salvadó, Jordi; Lapetra, José; Portillo, Maria P.; Estruch, Ramón
Abstract : Objective. To evaluate the long-term effects of a Mediterranean diet (MeDiet) intervention on the plasma concentrations of inflammatory and plaque stability-related molecules in elderly people at high risk for cardiovascular disease. Design and Setting . 66 participants from primary care centers affiliated with the Hospital Clinic of Barcelona were randomized into 3 groups: MeDiet plus extra virgin olive oil (EVOO) or nuts and a low-fat diet (LFD). At baseline and at 3 and 5 years, we evaluated the changes in the plasma concentrations of 24 inflammatory biomarkers related to the different stages of the atherosclerotic process by Luminex®. Results. At 3 and 5 years, both MeDiet groups showed a significant reduction of IL-6, IL-8, MCP-1, and MIP-1 β (P < 0.05 ; all) compared to LFD. IL-1 β, IL-5, IL-7, IL-12p70, IL-18, TNF- α, IFN- γ, GCSF, GMCSF, and ENA78 (P < 0.05 ; all) only decreased in the MeDiet+EVOO group and E-selectin and sVCAM-1 (P < 0.05 ; both) in the MeDiet+nuts group. Conclusions . Long-term adherence to MeDiet decreases the plasma concentrations of inflammatory biomarkers related to different steps of atheroma plaque development in elderly persons at high cardiovascular risk.